Ruderal vegetation of Ukraine: classes Galio-Urticetea Passarge ex Kopecký 1969 and Bidentetea R.Tx. et al. ex von Rochow 1951 - Dubyna, Dmytro Vasylovych; Dziuba, Tetiana Pavlivna; Iemelianova, Svitlana Mykolaivna; Felbaba-Klushyna, Lubov Mykhailivna; Tymoshenko, Pavlo Andriovych (Biodiversity: Research and Conservation, 2024)
The current state and syntaxonomic structure of anthropogenic vegetation of the classes Galio-Urticetea and Bidentetea are revealed. The class Galio-Urticetea is represented by 3 phytosociological orders, 6 alliances, and 32 associations. The class Bidentetea unites 8 plant associations of 1 order and 2 alliances. The territorial differentiation of the studied plant communities is caused by the limiting factors: soil moisture and the changing hydrological regime. Thus the phytocoenoses of these classes are confined to the natural zones of Polissia and forest-steppe. Based on detrended correspondence analysis, the leading factors differentiating vegetation units were identified. Within the class Galio-Urticetea, they include the continentality of climate, precipitation regime, and concentration of mineral nitrogen in the soil. The factors of major significance for Bidentetea were soil moisture and the concentration of mineral nitrogen in the substrate.